Freshwater shark teeth (Family Lonchidiidae) from the Middle-Upper Triassic (Ladinian-Carnian) Paramillo Formation in the Mendoza Precordillera, Argentina - Johns, Marjorie J. (2014)
A collection of over 550 elasmobranch teeth (Family Lonchidiidae) were obtained from fresh water fluvial deposits of the Middle–Upper Triassic (Ladinian–Carnian) Paramillo Formation, in northwestern Mendoza Province, Argentina. The new hybodontid species, Lonchidion paramilloensis, sp. nov., solely based on teeth, is within a 20-m-thick interval containing black shale interbedded with andesitic sills and intercalated with lensoidal calcarenites. The teeth have a characteristic labial peg with an accessory cusplet and a low gracile crown that is narrower labiolingually and more elongate laterally. The teeth are similar to some North American Late Triassic and Late Cretaceous species of the genus Lonchidion (e.g., L. humblei, L. griffisi, L. selachos), but are distinct in having a low primary cusp, up to seven pairs of lateral cusplets, a rounded-triangular-shaped labial peg with one accessory cusplet, and an absence of other crown ornaments. Color analyses of upper tooth crowns indicate an ichthyolith alteration index (IAI)/conodont alteration index (CAI) value of 6.0–6.5 (360–610°C). Considerable pitting and alteration of specimens indicates thermal alteration to 610°C and (or) chemical alteration.